Facing monstrosity in Goya's Los Caprichos (1799) - Lazaro-Reboll, Antonio (2004)
The aim of this thesis is to offer a re-evaluation of our cultural assumptions concerning the monstrous in the work of Francisco Jose de Goya y Lucientes (1746- 1828), specifically his collection of etchings Los Caprichos (1799). In my study there are three closely related areas of investigation: the image of the monstrous body in Goya's work; the cultural aspects of monsters and monstrous forms in Western discourses and in the Spanish Enlightenment; and the theoretical encounter between the history of the sciences and deconstructive criticism. The interaction between these three areas provides a background against which to understand the Goyaesque body within the context of Spanish cultural practices.